Creep cavitation damage of K-type thermocouples. (January 2023) - Rakshan Kumar, J.K.; Bhattacharjee, Debalina; Dsilva, Preetish; Praveen, R.; Hegde, Subray R.
Highlights: Industrial K-type thermocouples used in chemical processing plant were failing prematurely. Visual inspection, fractography and metallography confirmed that the thermoelements had undergone creep cavitation damage. Fractography and longitudinal micrographs confirmed the formation of r-type cavities predominantly along the transverse grain boundaries of the thermoelements. First principle calculation estimated the stress endured by the thermoelements and was confirmed to be in the coble creep regime in the deformation mechanism map. Selection of sheathing material (SS347) having significantly higher thermal expansion coefficient than that of the thermoelements (Chromel/Alumel) is adjudged as the root-cause for the in-service failure of the thermocouples. Abstract: This work investigates premature failure of K-Type thermocouples that were used in a chemical processing plant. The work presents a detailed metallurgical failure analysis involving, site visit, visual inspection, metallography, optical microscopy, scanning electron microscopy, and fractography. The analysis reveals that the thermocouple wires endured creep cavitation damage during service and eventually failed by creep-rupture. Interestingly, the influence of creep on the degradation of industrial thermocouples is not detected and reported thus far. By presenting analytical stress calculations using temperature dependent materials properties, the current work reveals that the thermal expansion mismatch between various materials of thermocouple causes high tensile stresses in the thermocouple wires during elevated temperature services. The work concludes that high tensile stresses at elevated temperature operation caused premature creep failure of the K-type thermocouples.